2014
DOI: 10.4236/ijohns.2014.35050
|View full text |Cite
|
Sign up to set email alerts
|

A Six-Year Review of Head and Neck Cancers at the Komfo Anokye Teaching Hospital, Kumasi, Ghana

Abstract: Background: In Ghana, information on the prevalence and pattern of Head and Neck Cancers (HNCA) is scarce. There are few publications based on specific sub-sites of the head and neck, however, literature on the prevalence and pattern of HNCA in general is lacking. The present study aimed to describe the pattern of HNCA among patients seen at the multidisciplinary HNCA clinic of Komfo Anokye Teaching Hospital. Methods: This is a retrospective review of all consecutive patient records seen at the multidisciplina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 18 publications
2
21
0
Order By: Relevance
“…In keeping with other authors in developing countries [ 12 , 35 , 38 ], the follow-up of patients in this study was generally poor as more than 60 percent of patients were lost to follow-up at the end of 5 years. We could not establish the reasons for the large number of loss to follow up in this study.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In keeping with other authors in developing countries [ 12 , 35 , 38 ], the follow-up of patients in this study was generally poor as more than 60 percent of patients were lost to follow-up at the end of 5 years. We could not establish the reasons for the large number of loss to follow up in this study.…”
Section: Discussionsupporting
confidence: 83%
“…Despite recent advances in the diagnosis and treatment of head and neck cancer, there has been little evidence of improvement in 5-year survival rates over the last few decades [ 35 , 38 ]. In this study, the overall 5-year survival rate of 20.6 % is significantly low compared to the survival rate for patients with advanced (stage III–IV) head and neck cancers managed in developed countries which ranges from 30 to 50 percent [ 19 , 35 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of head and neck squamous cell carcinoma (HNSCC) differ widely in Africa, from 0.8 per 100,000 in Ghana to 11.1 per 100,000 in South Africa [ 3 , 4 ]. Moreover, previous studies in Ghana have also shown that tumours of the pharynx, larynx and oral cavity formed the largest group of HNCs and most of the patients presented with late (stage IV) disease [ 5 , 6 ]. Molecular targeted therapy seeks to block tumour growth and spread by interfering with molecular carcinogenic pathways [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…With the current prevalence rate of 29% of all head and neck cancers [22] and 1.2–1.3% of all cancers in Ghana [23], and the number of cases in Korle-Bu Teaching Hospital (KBTH), Ghana, increasing steadily over the last few years, a study in this regard is very necessary to provide baseline data on the presence of HPV and EBV DNA in NPC tissue samples.…”
Section: Introductionmentioning
confidence: 99%